2022
DOI: 10.1111/zph.13009
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol exposure of live bird market workers to viable influenza A/H5N1 and A/H9N2 viruses, Cambodia

Abstract: Live bird markets (LBMs) have been identified as key factors in the spread, persistence and evolution of avian influenza viruses (AIVs). In addition, these settings have been associated with human infections with AIVs of pandemic concern. Exposure to aerosolised AIVs by workers in a Cambodian LBM was assessed using aerosol impact samplers. LBM vendors were asked to wear an air sampler for 30 min per day for 1 week while continuing their usual activities in the LBM during a period of high AIV circulation (Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Active air samplers function by using mechanical means, such as internal fans, blowers, or pumps to force air into a collection apparatus at various flow rates. [58,61] Typical flow rates range from 3.5 to 500 L min −1 (Table 1). For reference, humans breathe at a rate of 6 L min −1 .…”
Section: Active Aerosol Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Active air samplers function by using mechanical means, such as internal fans, blowers, or pumps to force air into a collection apparatus at various flow rates. [58,61] Typical flow rates range from 3.5 to 500 L min −1 (Table 1). For reference, humans breathe at a rate of 6 L min −1 .…”
Section: Active Aerosol Samplingmentioning
confidence: 99%
“…(2.371-4.217 μm) Horwood et al [58] Sioutas 86 mm (H) × 55 mm (∅) [69] 30 min 9 -Linde et al [38] Conical Inhalable Sampler (JS Holdings) with Gilian…”
Section: Electrostatic Collection Through Corona Chargingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the virus may have increased the ability to replicate and infect a broader range of species of birds [ 10 ]. A recent concern is that this strain has begun to infect mammals, including mink [ 11 ]. Currently, there is no evidence that A(H5N1) spreads between mammals, but this scenario is possible.…”
mentioning
confidence: 99%
“…The risk of infection has been assessed as low for the general population in the EU/EEA and as low to medium for those occupationally exposed to poultry [ 10 ]. Within the past month, Horwood and colleagues have reported that live bird markets in Cambodia have been identified as a source of airborne spread of avian influenza viruses [ 11 ]. The authors have identified viral spread and persistence in market workers during a period of high viral circulation, which supports the possibility of the evolution of avian influenza viruses in live bird markets [ 11 ].…”
mentioning
confidence: 99%